Authoritarian innovations in Indonesia: electoral narrowing, identity politics and executive illiberalism. Issue 6 (17th August 2020) - Mietzner, Marcus
ABSTRACT: In the last decade, autocrats and democrats alike have used a wide range of innovative illiberal methods to cement or expand their power. Especially in democracies, however, these techniques have often been difficult to detect as they are typically packaged as acts of democracy defense, not erosion. This article discusses the deployment of authoritarian innovations in Indonesia, where the elite as a collective, the opposition and the executive each launched illiberal initiatives that caused a notable decline in the country's democratic quality. These illiberal strategies concern a narrowing of electoral competitiveness, the mobilization of identity politics, and attempts at power concentration and maximization by the executive. The wide spread of anti-democratic actors in Indonesia differs from other cases of increasing illiberalism, in which executive leaders have been the main drivers. But Indonesia also stands out because the residual resources of its defective but persistent electoral democracy have mitigated the effectiveness of the authoritarian innovations, preventing (thus far) the polity's full descent into autocracy or populist illiberalism.